Modified aramid diaphragm coating slurry, battery diaphragm and preparation method of modified aramid diaphragm coating slurry

The modified aramid-coated slurry is prepared by polymerization, and the ventilation of the membrane is improved by using nanoparticles, which solves the problem of poor breathability of the aramid-coated slurry in the prior art, and improves heat resistance and breathability. The process is also achieved. Simple and efficient.

CN119176937AActive Publication Date: 2024-12-24YANTAI TAYHO ADVANCED MATERIALS RES INST CO LTD

Patent Information

Application Number
CN202411696933.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-24
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing aramid-coated diaphragm has poor breathability, difficulty in dispersing ceramics in the stock solution, long and uneven dispersion cycles, which affects the performance of the diaphragm.

Method used

Modified aramid coating slurry was prepared by polymerization. By adjusting solvents, co-solvents and adding third monomers, nanoparticles were formed as pore-forming agents, replacing inorganic ceramic particles, and improving the breathable performance of the separator.

Benefits of technology

A modified aramid diaphragm with both heat resistance and breathability was prepared. The process was simple, time-saving and efficient, avoiding the problem of poor dispersion of ceramics and achieving excellent performance of the diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176937A_ABST
    Figure CN119176937A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery diaphragm preparation, in particular to modified aramid diaphragm coating slurry, a battery diaphragm and a preparation method thereof.The preparation method of the modified aramid diaphragm coating slurry comprises the steps that under protection of inert gas, a cosolvent is dissolved into a polymerization solvent, and a solvent-cosolvent mixed system is obtained; adding p-phenylenediamine into the solvent-cosolvent mixed system, and dissolving to obtain a mixed solution; adding paraphthaloyl chloride into the mixed solution in batches, controlling the temperature of the system, and carrying out polymerization reaction, so as to obtain the modified aramid diaphragm coating slurry after the polymerization reaction is finished, in the preparation method, a third monomer is also added to participate in the polymerization reaction, and the third monomer is at least one of an amine third monomer and an acyl chloride third monomer. The modified aramid diaphragm coating slurry can be used for preparing a battery diaphragm with heat resistance and air permeability, and the process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified aramid diaphragm coating slurry, a battery diaphragm and a preparation method thereof, and belongs to the technical field of battery diaphragm preparation. Background Art

[0002] Lithium-ion batteries have the characteristics of high specific energy, high cycle life, small size, light weight, no memory effect, and no pollution. They are alternative products to mainstream nickel-cadmium and nickel-hydrogen batteries. They have great potential in the development of energy storage equipment and have rapidly developed into a new generation of energy storage power sources. They can be used for power support in information technology, electric vehicles and hybrid vehicles, aerospace and other fields. As one of the key inner components of lithium-ion batteries, the diaphragm plays a vital role in the performance of lithium-ion batteries. The capacity, cycle performance, and safety performance of the battery are closely related to the performance of the diaphragm.

[0003] Traditional diaphragm materials are polyolefin diaphragms, such as polyethylene PE, polypropylene PP, and composite diaphragms of the two. However, polyolefin diaphragms have a large difference in polarity with the electrolyte, poor wettability with the electrolyte, poor thermal stability at high temperatures, and easy shrinkage, resulting in unstable diaphragm dimensions, which can easily cause short circuits between electrodes, leading to thermal runaway of the battery, and finally causing safety issues such as fire and explosion. Therefore, technicians are looking for new heat-resistant materials to be coated on the surface of PE and PP diaphragm materials to improve the temperature resistance of the diaphragm.

[0004] Aramid is an aromatic polyamide fiber with high strength, high modulus, high temperature resistance, flame retardancy and other excellent properties. The commonly referred to aramid includes poly(m-phenylene isophthalamide) (aramid 1313), poly(p-phenylene terephthalamide) (aramid 1414, aramid II) and heterocyclic aramid (aramid III). Among them, aramid 1414 is a high-temperature resistant fiber variety with early development, wide application, large output and rapid development. It has excellent high temperature resistance and corrosion resistance. Coating it on the diaphragm can significantly improve the heat resistance of the diaphragm. However, the aramid coated diaphragm has high density, resulting in poor air permeability of the diaphragm. Chinese patent application CN118943660A discloses an aramid coated slurry, diaphragm and its preparation method and application. The patent proposes to add ceramics as a pore-forming agent to the aramid stock solution to improve the air permeability of the diaphragm. The problem with this method is that it is difficult to disperse the ceramics in the stock solution, the dispersion cycle is long and the dispersion is uneven, which affects the performance of the diaphragm.

[0005] Therefore, it is necessary to prepare a new aramid coating slurry so that the aramid coated diaphragm has both excellent thermal properties and air permeability. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a modified aramid diaphragm coating slurry, a battery diaphragm and a preparation method thereof. The modified aramid diaphragm coating slurry can be used to prepare a battery diaphragm with both heat resistance and air permeability, and the process is simple. It also solves the problems of poor dispersibility and long dispersion cycle of the existing ceramic aramid diaphragm coating slurry.

[0007] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a modified aramid diaphragm coating slurry, the preparation method comprising: S1. Under the protection of inert gas, dissolving the co-solvent into the polymerization solvent to obtain a solvent-co-solvent mixed system; S2, adding p-phenylenediamine to the solvent-cosolvent mixed system to dissolve it to obtain a mixed solution; S3, adding terephthaloyl chloride to the mixed solution in batches, controlling the system temperature to carry out polymerization reaction, and obtaining the modified aramid diaphragm coating slurry after the polymerization reaction is completed; In the preparation method, a third monomer is also added to participate in the polymerization reaction, and the third monomer is at least one of an amine third monomer and an acyl chloride third monomer; when an amine third monomer is used, the amine third monomer is added in step S2; when an acyl chloride third monomer is used, the acyl chloride third monomer is added in batches in step S3; The amine third monomer is at least one of 2-chloro-p-phenylenediamine, aniline, and piperazine; The acyl chloride third monomer is at least one of benzoyl chloride, 4-chlorobenzoyl chloride and p-methylbenzoyl chloride.

[0008] Furthermore, the co-solvent is at least one of calcium chloride and lithium chloride; the polymerization solvent is at least one of N-methylpyrrolidone and N,N-dimethylacetamide.

[0009] Furthermore, the amount of the co-solvent added is 3%-8% of the mass of the polymerization solvent.

[0010] Furthermore, the total amount of the p-phenylenediamine and the amine third monomer in the solvent-cosolvent mixed system is 0.1-0.5 mol / L.

[0011] Furthermore, the molar ratio of the p-phenylenediamine to the amine third monomer is (4-9):1.

[0012] Furthermore, the molar ratio of terephthaloyl chloride to the acyl chloride-based third monomer is (4-9):1.

[0013] Furthermore, the ratio of the total molar number of terephthaloyl chloride and the acyl chloride-type third monomer to the total molar number of p-phenylenediamine and the amine-type third monomer is (0.9~1.1):1.

[0014] The invention also discloses a modified aramid diaphragm coating slurry, and the modified aramid diaphragm coating slurry is prepared according to the preparation method of the invention.

[0015] The invention also discloses a method for preparing a battery separator, which comprises: uniformly coating the modified aramid separator coating slurry on both sides of a base film, and then curing the base film in a coagulation bath, washing the base film with water, and drying the base film to obtain the battery separator.

[0016] The invention also discloses a battery separator, which is prepared according to the preparation method of the invention.

[0017] The beneficial effects of the present invention are: The present invention prepares a para-aramid coating slurry by a polymerization method, and during the polymerization process, the solvent, the co-solvent, and the third monomer are adjusted to copolymerize directly in the slurry to form nanoparticles, which replace inorganic ceramic particles to improve the air permeability of the coated membrane. The present invention adopts a "one-pot method" for preparation, which is simple in process, time-saving and efficient, and avoids the problems of long dispersion period and uneven dispersion of traditional inorganic ceramic particles added to the aramid stock solution. The prepared modified aramid coated membrane has excellent heat resistance and air permeability.

[0018] The method for preparing the modified aramid diaphragm coating slurry of the present invention uses p-phenylenediamine and terephthaloyl chloride as polymerization monomers, and adopts low-temperature solution polycondensation to prepare p-aramid stock solution; copolymerization modification is carried out by adding a third monomer to replace the position of p-phenylene, thereby destroying the regularity of the p-aramid molecular chain, and changing the molecular chain structure from a rigid rod to a spiral, thereby increasing flexibility; at the same time, adjusting the dosage of the polymerization solvent and the co-solvent to achieve the dissolution of the p-aramid in the solvent, and under the synergistic effect of these process conditions, some nanoparticles are polymerized to serve as pore-forming agents, so as to prepare a modified aramid coated battery diaphragm with both heat resistance and air permeability, which has broad application prospects in the field of battery diaphragms.

[0019] This method prepares the aramid diaphragm coating slurry through a "one-pot method", which has the advantages of simple process, time saving and high efficiency, and the prepared diaphragm has excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a microscopic morphology of the modified aramid coated battery separator of Example 1; Figure 2 This is the microscopic morphology of the pure aramid coated battery separator of Comparative Example 1.

[0021] Figure 3 This is the microscopic morphology of the ceramic / aramid coated battery separator of Comparative Example 2. DETAILED DESCRIPTION

[0022] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0024] A method for preparing a modified aramid diaphragm coating slurry, the preparation method comprising: S1. Under the protection of inert gas, dissolving the co-solvent into the polymerization solvent to obtain a solvent-co-solvent mixed system; S2, adding p-phenylenediamine to the solvent-cosolvent mixed system to dissolve it to obtain a mixed solution; S3, adding terephthaloyl chloride to the mixed solution in batches, controlling the system temperature to carry out polymerization reaction, and obtaining the modified aramid diaphragm coating slurry after the polymerization reaction is completed; In the preparation method, a third monomer is also added to participate in the polymerization reaction, and the third monomer is at least one of an amine third monomer and an acyl chloride third monomer; when an amine third monomer is used, the amine third monomer is added in step S2; when an acyl chloride third monomer is used, the acyl chloride third monomer is added in batches in step S3; The amine third monomer is at least one of 2-chloro-p-phenylenediamine, aniline, and piperazine; The acyl chloride third monomer is at least one of benzoyl chloride, 4-chlorobenzoyl chloride and p-methylbenzoyl chloride.

[0025] Specifically, the co-solvent is at least one of calcium chloride and lithium chloride; the polymerization solvent is at least one of N-methylpyrrolidone and N,N-dimethylacetamide.

[0026] Specifically, the amount of the co-solvent added is 3%-8% of the mass of the polymerization solvent.

[0027] Specifically, the total amount of the p-phenylenediamine and the amine third monomer in the solvent-cosolvent mixed system is 0.1-0.5 mol / L.

[0028] Specifically, the molar ratio of the p-phenylenediamine to the amine third monomer is (4-9):1.

[0029] Specifically, the molar ratio of terephthaloyl chloride to the acyl chloride-based third monomer is (4-9):1.

[0030] Specifically, the ratio of the total molar number of terephthaloyl chloride and the acyl chloride-type third monomer to the total molar number of p-phenylenediamine and the amine-type third monomer is (0.9-1.1):1.

[0031] More specifically, the polymerization reaction is low-temperature polymerization, and the reaction temperature is -10~0°C, and -5°C is used in the embodiment of the present invention.

[0032] A modified aramid diaphragm coating slurry is prepared according to the preparation method of the present invention.

[0033] A method for preparing a battery separator comprises the following steps: uniformly coating the modified aramid separator coating slurry of the present invention on both sides of a base film, and then curing the base film in a coagulation bath, followed by washing and drying to obtain the battery separator.

[0034] Specifically, the base film is a polyolefin base film, and the thickness of the polyolefin base film is 5-40 μm.

[0035] More specifically, the polyolefin-based film is selected from polyethylene film, polypropylene film or polypropylene / polyethylene / polypropylene composite film.

[0036] More specifically, in the embodiment of the present invention, the coagulation bath is an aqueous solution of a polymerization solvent, the mass concentration of the polymerization solvent in the coagulation bath is 40%, and the temperature of the coagulation bath is 30°C.

[0037] A battery separator is prepared according to the preparation method of the present invention.

[0038] Example 1 A method for preparing a modified aramid diaphragm coating slurry and a battery diaphragm, specifically comprising the following steps: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 3.9796 g p-phenylenediamine and 0.3522 g piperazine (the molar ratio of p-phenylenediamine to piperazine is 9:1), and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 8.3595 g of terephthaloyl chloride (the ratio of the molar number of terephthaloyl chloride to the total molar number of p-phenylenediamine and piperazine was 1.007:1) was added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0039] Example 2 A method for preparing a modified aramid diaphragm coating slurry and a battery diaphragm, specifically comprising the following steps: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cooling the NMP-CaCl2 mixed system to 20°C, accurately adding 3.9796 g of p-phenylenediamine and 0.5830 g of 2-chloro-p-phenylenediamine (the molar ratio of p-phenylenediamine to 2-chloro-p-phenylenediamine is 9:1), stirring and dissolving under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 8.3595 g of terephthaloyl chloride (the ratio of the molar number of terephthaloyl chloride to the total molar number of p-phenylenediamine and 2-chloro-p-phenylenediamine was 1.007:1) was added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polypropylene separator with a thickness of 9 μm was selected, and the modified aramid separator coating slurry was coated on both sides of the base film by a wire roller coating method. The coated separator was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery separator was obtained after drying.

[0040] Example 3 A method for preparing a modified aramid diaphragm coating slurry and a battery diaphragm, specifically comprising the following steps: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cooling the NMP-CaCl2 mixed system to 20°C, accurately adding 3.9796 g of p-phenylenediamine and 0.7616 g of aniline (the molar ratio of p-phenylenediamine to aniline is 8:2), stirring and dissolving under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 8.3595 g of terephthaloyl chloride (the ratio of the molar number of terephthaloyl chloride to the total molar number of p-phenylenediamine and aniline was 1.007:1) was added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polypropylene / polyethylene / polypropylene composite film with a thickness of 9 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0041] Example 4 A method for preparing a modified aramid diaphragm coating slurry and a battery diaphragm, specifically comprising the following steps: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 4.4218 g of p-phenylenediamine, and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 7.5236 g of terephthaloyl chloride and 0.5788 g of benzoyl chloride were added in batches under stirring conditions (the molar ratio of terephthaloyl chloride to benzoyl chloride was 9:1, and the ratio of the total molar number of terephthaloyl chloride and benzoyl chloride to the molar number of p-phenylenediamine was 1.007:1), and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0042] Example 5 A method for preparing a modified aramid diaphragm coating slurry and a battery diaphragm, specifically comprising the following steps: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 4.4218 g of p-phenylenediamine, and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 7.5236 g of terephthaloyl chloride and 0.7206 g of 4-chlorobenzoyl chloride were added in batches under stirring conditions (the molar ratio of terephthaloyl chloride to 4-chlorobenzoyl chloride was 9:1, and the ratio of the total molar number of terephthaloyl chloride and 4-chlorobenzoyl chloride to the molar number of p-phenylenediamine was 1.007:1), and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 12 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0043] Example 6 A method for preparing a modified aramid diaphragm coating slurry and a battery diaphragm, specifically comprising the following steps: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 4.4218 g of p-phenylenediamine, and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 7.4190 g of terephthaloyl chloride and 0.6277 g of p-toluoyl chloride were added in batches under stirring (the molar ratio of terephthaloyl chloride to p-toluoyl chloride was 9:1, and the ratio of the total molar number of terephthaloyl chloride and p-toluoyl chloride to the molar number of p-phenylenediamine was 0.993:1), and low-temperature solution polymerization was started under N2 protection and strong stirring until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0044] Example 7 A method for preparing a modified aramid diaphragm coating slurry and a battery diaphragm, specifically comprising the following steps: (1) Weigh 10 g of anhydrous LiCl, add DMAc to 200 g, heat and stir to dissolve under N2 protection to obtain a DMAc-LiCl mixed system; (2) Cooling the NMP-LiCl mixed system to 20°C, accurately adding 3.9796 g of p-phenylenediamine and 0.3522 g of aniline (the molar ratio of p-phenylenediamine to aniline is 9:1), stirring and dissolving under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 7.5236 g of terephthaloyl chloride and 0.5788 g of benzoyl chloride (the molar ratio of terephthaloyl chloride to benzoyl chloride was 9:1, and the molar ratio of acyl chloride monomer to amine monomer was 1.007:1) were added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0045] Example 8 A method for preparing a modified aramid diaphragm coating slurry and a battery diaphragm, specifically comprising the following steps: (1) Weigh 14 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 6.9210 g of p-phenylenediamine, 0.7450 g of aniline and 1.1406 g of 2-chloro-p-phenylenediamine (the molar ratio of the three is 8:1:1), stir and dissolve under N2 protection to obtain a 0.4 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, 16.3553 g of terephthaloyl chloride (the molar ratio of terephthaloyl chloride to amine monomer was 1.007:1) was added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0046] Comparative Example 1 The difference between this comparative example 1 and example 1 is that a pure diaphragm coating slurry is prepared without adding an amine third monomer or an acyl chloride third monomer. The specific implementation method is as follows: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 4.4218 g of p-phenylenediamine, and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, 8.3595 g of terephthaloyl chloride (the molar ratio of terephthaloyl chloride to p-phenylenediamine was 1.007:1) was added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain an aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the aramid slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the aramid coated battery diaphragm was obtained after drying.

[0047] Comparative Example 2 In this comparative example 2, inorganic ceramic particles are added on the basis of comparative example 1 to improve the air permeability of the aramid coated diaphragm. The specific implementation method is: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system with a mass fraction of 5%; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 4.4218 g of p-phenylenediamine, and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, 8.3595 g of terephthaloyl chloride (the molar ratio of terephthaloyl chloride to p-phenylenediamine was 1.007:1) was added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain an aramid diaphragm coating slurry; (4) adding 2% by mass of nano-alumina to the aramid slurry of step (3), stirring for 120 min using a high-speed dispersing emulsifier to obtain a ceramic / aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the ceramic / aramid membrane coating slurry was coated on both sides of the base film by a wire roller coating method. The coated membrane was immersed in a coagulation bath for solidification and then dried to obtain a ceramic / aramid coated battery separator.

[0048] Comparative Example 3 The difference between this comparative example 3 and Example 1 is that when preparing the membrane coating slurry, the amount of the co-solvent is increased. In this comparative example 3, the amount of the co-solvent added is 10% of the mass of the polymerization solvent. The specific preparation process is as follows: (1) Weigh 20 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 3.9796 g p-phenylenediamine and 0.3522 g piperazine (the molar ratio of p-phenylenediamine to piperazine is 9:1), and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 8.3595 g of terephthaloyl chloride (the molar ratio of terephthaloyl chloride to p-phenylenediamine and piperazine was 1.007:1) was added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0049] Comparative Example 4 The difference between this comparative example 4 and Example 1 is that when preparing the pure membrane coating slurry, the amount of the co-solvent is reduced. In this comparative example 3, the amount of the co-solvent added is 2% of the mass of the polymerization solvent. The specific preparation process is as follows: (1) Weigh 4 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 3.9796 g p-phenylenediamine and 0.3522 g piperazine (the molar ratio of p-phenylenediamine to piperazine is 9:1), and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 8.3595 g of terephthaloyl chloride (the molar ratio of terephthaloyl chloride to p-phenylenediamine and piperazine was 1.007:1) was added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; It was found in the experiment that the modified aramid diaphragm coating slurry prepared in Comparative Example 4 had a high viscosity and could not be evenly coated on the base film.

[0050] Comparative Example 5 The difference between this comparative example 5 and example 1 is that in step (2), the addition ratio of piperazine is increased and the addition ratio of p-phenylenediamine is reduced. The specific preparation process is as follows: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 0.4326 g p-phenylenediamine and 3.1009 g piperazine (the molar ratio of p-phenylenediamine to piperazine is 1:9), and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 8.3595 g of terephthaloyl chloride (the ratio of the molar number of terephthaloyl chloride to the total molar number of p-phenylenediamine and piperazine was 1.007:1) was added in batches under stirring conditions, and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0051] Comparative Example 6 The difference between this comparative example 6 and example 4 is that in step (2), the addition ratio of benzoyl chloride is increased and the addition ratio of terephthaloyl chloride is reduced. The specific preparation process is as follows: (1) Weigh 10 g of anhydrous CaCl2, add NMP to 200 g, heat and stir to dissolve under N2 protection to obtain a NMP-CaCl2 mixed system; (2) Cool the NMP-CaCl2 mixed system to 20°C, accurately add 4.4218 g of p-phenylenediamine, and stir and dissolve under N2 protection to obtain a 0.2 mol / L mixed solution; (3) The mixed solution in step (2) was cooled to -5°C, and 0.8178 g of terephthaloyl chloride and 5.0958 g of benzoyl chloride were added in batches under stirring conditions (the molar ratio of terephthaloyl chloride to benzoyl chloride was 1:9, and the ratio of the total molar number of terephthaloyl chloride and benzoyl chloride to the molar number of p-phenylenediamine was 1.007:1), and low-temperature solution polymerization was started under N2 protection and strong stirring conditions until the Weissenberg phenomenon appeared and the reaction was stopped to obtain a modified aramid diaphragm coating slurry; (4) A polyethylene base film with a thickness of 9 μm was selected, and the modified aramid diaphragm coating slurry was coated on both sides of the base film by a wire roller coating method. The coated diaphragm was immersed in a coagulation bath for curing and forming, and the modified aramid coated battery diaphragm was obtained after drying.

[0052] For the products in each embodiment and comparative example, a thickness measuring instrument was used to test the thickness of the diaphragm; an air permeability tester was used to test the air permeability of the diaphragm; and an oven and a ruler were used to calculate the thermal shrinkage of the diaphragm. The test indicators are summarized in the following Table 1.

[0053] Table 1 Battery separator performance test data

[0054] From the above data, it can be seen that the modified aramid coated battery separators prepared by the preparation method of the present invention in Examples 1 to 8 have excellent air permeability and heat resistance. Compared with Comparative Example 1, the air permeability of the modified aramid coated separators is lower than that of the pure aramid coated separators, indicating that the air permeability is improved, proving that the nanoparticles generated by the polymerization of the modified aramid can effectively improve the air permeability, while avoiding the problem of the long dispersion period of the inorganic ceramics added later in Comparative Example 2. The air permeability of the modified aramid coated separator prepared by the method of the present invention reached 140.3s / 100cc (Example 7), which is better than 269.6 s / 100cc of Comparative Example 2. This is because the uniformity of the nanoparticles generated by polymerization in the slurry is better than that of the inorganic ceramic particles added later.

[0055] From the data comparison of Comparative Example 3 and Example 1, it can be seen that if the amount of co-solvent used is too much, the air permeability of the diaphragm will decrease, because the solubility of para-aramid in the solvent increases, the degree of polymerization increases, and the density of the coated diaphragm increases.

[0056] From the comparison of the experimental conditions of Comparative Example 4 and Example 1, it can be seen that if the amount of co-solvent used is too small, the prepared modified aramid diaphragm coating slurry is too viscous and cannot be coated on the base membrane because the solubility of para-aramid in the solvent is reduced and the fluidity becomes poor.

[0057] From the data comparison between Comparative Example 5 and Example 1, and Comparative Example 6 and Example 4, it can be seen that if the dosage ratio of the third monomer is increased, the heat resistance of the diaphragm decreases. Therefore, by adopting the dosage ratio of the third monomer specified in the present invention, the diaphragm can have better air permeability and excellent heat resistance.

[0058] In summary, the present invention discloses a modified aramid membrane coating slurry, a battery membrane and a preparation method thereof, which introduces a third monomer with low reactivity into the aramid polymerization for copolymerization modification, adjusts the polymerization solvent and the cosolvent at the same time, forms some nanoparticles as pore-forming agents for the membrane coating slurry during the para-aramid polymerization process, and prepares a modified aramid membrane coating slurry with both heat resistance and air permeability. This method prepares the aramid membrane coating slurry by a "one-pot method", has the advantages of simple process, time saving and high efficiency, and the prepared membrane has excellent performance.

[0059] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0060] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a modified aramid diaphragm coating slurry, characterized in that: The preparation method is: S1. Under the protection of inert gas, dissolving the co-solvent into the polymerization solvent to obtain a solvent-co-solvent mixed system; S2, adding p-phenylenediamine to the solvent-cosolvent mixed system to dissolve it to obtain a mixed solution; S3, adding terephthaloyl chloride to the mixed solution in batches, controlling the system temperature to carry out polymerization reaction, and obtaining the modified aramid diaphragm coating slurry after the polymerization reaction is completed; In the preparation method, a third monomer is also added to participate in the polymerization reaction, and the third monomer is at least one of an amine third monomer and an acyl chloride third monomer; when an amine third monomer is used, the amine third monomer is added in step S2; when an acyl chloride third monomer is used, the acyl chloride third monomer is added in batches in step S3; The amine third monomer is at least one of 2-chloro-p-phenylenediamine, aniline, and piperazine; The acyl chloride third monomer is at least one of benzoyl chloride, 4-chlorobenzoyl chloride and p-methylbenzoyl chloride.

2. The method for preparing a modified aramid diaphragm coating slurry according to claim 1, characterized in that: The co-solvent is at least one of calcium chloride and lithium chloride; the polymerization solvent is at least one of N-methylpyrrolidone and N,N-dimethylacetamide.

3. The method for preparing a modified aramid diaphragm coating slurry according to claim 1, characterized in that: The amount of the co-solvent added is 3%-8% of the mass of the polymerization solvent.

4. The method for preparing a modified aramid diaphragm coating slurry according to claim 1, characterized in that: The total amount of the p-phenylenediamine and the amine third monomer in the solvent-cosolvent mixed system is 0.1-0.5 mol / L.

5. The method for preparing a modified aramid diaphragm coating slurry according to claim 1, characterized in that: The molar ratio of the p-phenylenediamine to the amine third monomer is (4-9):

1.

6. The method for preparing a modified aramid diaphragm coating slurry according to claim 1, characterized in that: The molar ratio of terephthaloyl chloride to the acyl chloride-type third monomer is (4-9):

1.

7. The method for preparing a modified aramid diaphragm coating slurry according to claim 1, characterized in that: The ratio of the total molar number of terephthaloyl chloride and the acyl chloride-type third monomer to the total molar number of p-phenylenediamine and the amine-type third monomer is (0.9~1.1):

1.

8. A modified aramid diaphragm coating slurry, characterized in that: The modified aramid diaphragm coating slurry is prepared according to the preparation method according to any one of claims 1-7.

9. A method for preparing a battery separator, characterized in that: The preparation method comprises: uniformly coating the modified aramid diaphragm coating slurry as claimed in claim 8 on both sides of the base film, and then washing and drying after curing in a coagulation bath to obtain a battery diaphragm.

10. A battery separator, characterized in that: The battery separator is prepared according to the preparation method described in claim 9.

Citation Information

Patent Citations

  • Modified para-aramid polymer solution, coating slurry, lithium battery diaphragm and preparation method of lithium battery diaphragm

    CN112694610A

  • Lithium ion secondary battery separator

    JP2019212479A

  • Method for producing wholly aromatic polyamide porous film, heat-resistant separator including porous film, and porous film

    JP2020063400A

  • Coating liquid for separator, manufacturing method of the separator, separator obtained by the manufacturing method

    JP2020102427A

  • Aramid fiber polymer coated lithium ion battery membrane and preparation method therefor

    WO2017016373A1

Cited By

  • Aramid fiber water-dispersible nano-microsphere, coating slurry, diaphragm and preparation method of aramid fiber water-dispersible nano-microsphere

    CN119661869A

  • A battery module high temperature resistant film and preparation method thereof

    CN119775612A

  • Copolymerized para-aramid coating liquid as well as preparation method and application thereof

    CN120192706A

  • Lithium battery positive electrode slurry, positive electrode plate, preparation method and application

    CN120565568A

  • Aromatic polyamide ultrafiltration membrane and preparation method thereof

    CN120827804A